Antecedents and consequences of brand experience: a conceptual study of fast food Industry in Malaysia / Rozita Naina Mohamed … [et al.] - Naina Mohamed, Rozita; Mohd Daud, Norzaidi; Abdul Rahim, Faizah; Musa, Rosidah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Malaysian foodservice industry offers great potential for investors as it continues to develop and saw positive growth from 2000 to 2005, with 100% home delivery/takeaway and cafes/bars seeing the greatest growth, i.e. 97% and 61% over the period respectively. Evidently, fast food industry experienced the fastest growth and contributing economically to the nation. Since the competitions’ is getting stiff, the industry has to precisely understand the consumers’ lifestyle and consumption experience. The lack of awareness on the sensitivity of customers’ consumption experience has let companies, individuals or products down. Notably, brand experience is still new and emerging. However, the antecedents and consequences of brand experience are still elusive. This study conceptualized the perception of customers on the antecedents influence of brand experience (product quality, service quality and corporate social responsibility) and consequences that influence resonance of the four prominent fast food in Malaysia namely, Me Donald’s, Kentucky Fried Chicken, Kenny Rogers Roaster and Pizza Hut. The result of this study will provide insight into the brand experience factors that could influence successful implementation of branding models specifically for the fast food industry. Indeed, the research findings could also unveil the opportunity for the fast food businesses to undergo an operation-check in order to reformulate their branding strategies. For academicians and students, the conceptual insights derived from this study would add to the literature and would allow better understanding of the pre-requisites necessary to succeed, sustainability and the capability of businesses to increase its revenues and earnings thereby ensuring corporate longevity in today’s competitive environment.